Thrombus on Mitral Prosthetic Valve An Uncommon Complication (Cardiovascular Journal, 2011)
Sudden withdrawal of oral anticoagulant in patients with metalic prosthetic valve without adequate coverage with parenteral heparin may lead to fatal consequences. Here the authors report a uncommon case of thrombotic mitral prosthetic occlusion due to sudden withdrawal of warfarin. Keywords: Prosthetic valve, Thrombus, Thrombolytic. DOI: http://dx.doi.org/10.3329/cardio.v1i1.8219 Cardiovasc. j. 2008; 1(1) : 109-111